3차 회선 보간법에 적응적 매개변수를 적용한 영상 보간 - 유재욱(Jea-Wook Yoo); 박대현(Dae-Hyun Park); 김윤(Yoon Kim) (韓國컴퓨터情報學會論文誌, 2008)
In this paper, we present an adaptive parametric cubic convolution technique in order to enlarge the low resolution image to the high resolution image. The proposed method consists of two steps. During the first interpolation step, we acquire adaptive parameters in introducing a new cost-function to reflect frequency properties. And, the second interpolation step performs cubic convolution by applying the parameters obtained from the first step. The enhanced interpolation kernel using adaptive parameters produces output image better than the conventional one using a fixed parameter. Experimental results show that the proposed method can not only provides the performances of $0.5{\sim}4dB$ improvements in terms of PSNR, but also exhibit better edge preservation ability and original image similarity than conventional methods in the enlarged images. 본 논문에서는 고화질, 고해상도로 영상을 확대하기 위한 적응적인 매개변수가 적용된 3차 회선 보간법을 제안한다. 제안하는 보간법에서는 영상이 가지는 주파수 특성을 반영한 보간을 수행하기 위해 1단계 보간 과정에서 새롭게 정의한 비용함수를 이용하여 3차 회선 보간법의 매개변수를 적응적으로 구하고, 2단계 보간 과정에서는 1단계에서 구한 적응적인 매개변수를 적용하여 3차 회선 보간법을 수행한다. 영상의 주파수 특성이 고려된 적응적인 매개변수의 사용은 보간 커널의 성능을 향상시켜 동일한 매개변수를 사용하는 이전의 3차 회선 보간법보다 결과 영상의 화질이 우수하다. 컴퓨터 실험 결과를 통해 제안하는 보간법이 이전의 보간법들보다 PSNR이 약 $0.5{\sim}4dB$ 높아 객관적인 성능에서 나은 결과를 나타냈으며, 결과 영상의 확대를 통한 비교에서 영상이 부드럽고 에지가 선명하게 나타남으로 주관적 화질이 우수함을 보였다.